Emotional modulation of cortical activity during gum chewing: A functional near-infrared spectroscopy study - Hasegawa, Yoko; Sakuramoto, Ayumi; Suzuki, Tatsuya; Sakagami, Joe; Shiramizu, Masako; Tachibana, Yoshihisa; Kishimoto, Hiromitsu; Ono, Yumie; Ono, Takahiro (Frontiers in Neuroscience, 2022)
Distinct brain regions are known to be associated with various emotional states. Cortical activity may be modulated by emotional states that are triggered by flavors during food intake. We examined cortical activity during chewing with different tastes/odors using multichannel near-infrared spectroscopy. Thirty-six right-handed volunteers participated in this crossover trial. The participants experienced positive and negative emotions from chewing flavorful (palatable) or less flavorful (unpalatable) gums, respectively for 5 minutes. Participants rated the taste, odor, and deliciousness of each gum using a visual analog scale. Bilateral hemodynamic responses in the frontal and parietal lobes, bilateral masseter muscle activation, and heart rate were measured during gum chewing. Changes in all measured data during gum chewing were also evaluated. The ratings of the tastes and odors of each gum significantly differed among the participants (p<0.001). Hemodynamic responses were significantly elevated in the bilateral primary sensorimotor cortex during chewing as compared to resting. Although the hemodynamic responses of wide brain regions showed little difference between resting and gum chewing states, a difference was detected in the corresponding left frontopolar/dorsolateral prefrontal cortex. Muscle activation and heart rate were not significantly different between different gum types. Differential processing in the left prefrontal cortex might be responsible for the emotional states caused by palatable and unpalatable foods.